Exploring the Parameters of Morality and Decency as Reasonable Restrictions on Freedom of Expression - Smita Srivastava, (AG Volumes, 2026)
Laws that impose reasonable restrictions in the interest of “decency” and “morality” are one of the exceptions to the fundamental right to freedom of speech and expression protected by Article 19(1)(a) of the Constitution of India. However, at one hand vulgarity in the name of freedom of speech and expression and emergence of moral policing in the name of Indian values has created the serious issue for freedom of speech and expression. There is need to create a balance between personal liberty and communal standards of morality and decency. This research article explores the delicate balance between protecting freedom of expression and imposing reasonable restrictions in the name of morality and decency. The article aims to contribute to the ongoing discussion on the boundaries of free speech by critically examining the role of morality and decency as legitimate grounds for restrictions in a democratic society.